Quality of work for Syrian refugees in Jordan - Kattaa, M; Byrne, M (Refugee Studies Centre, University of Oxford, 2018)
Work permits have been at the centre of the policy debate on the hosting of Syrian refugees in Jordan. This approach needs also to involve ensuring decent working conditions for all.